The application of cattle manure to improve soil fertility for crop production in Uganda - Muhereza, Innocent; Pritchard, Deborah; Murray-Prior, Roy; Bowden, B. (Australian Society of Soil Science Inc, 2011)
Declining per capita food production and soil fertility depletion are threatening the livelihoods of many small-holder farmers in East Africa, including Uganda. High demand for food due to the increase in population has necessitated the need to improve crop yields where synthetically manufactured fertiliser use in the production system is often scarce and expensive. Cattle manure provides essential plant nutrients (mainly nitrogen, phosphorous and potassium) and is available locally; however, there is little information in Uganda on soil fertility status, the most effective rates of cattle manure, methods of application, crop requirements for specific nutrients and limiting factors to crop production. A survey was conducted on selected small-holder farmers in Uganda, in the central districts (Kampala and Wakiso) in January 2010 to identify socio-economic factors influencing the use of fertiliser and the current level of soil fertility as constraints that were most limiting to plant production. It was apparent from the survey and soil sampling that soil physicochemical values varied greatly amongst the soils and sites investigated. Unfortunately, in many situations the application of fertilisers being used didn’t target specific nutrients most limiting to crop production. The main findings from the soil survey will be presented in this paper and subsequent field research and nitrogen modelling that has been conducted to better assist farmers in Uganda improve crop productivity through more effective fertiliser practice.